Meat quality analysis : advanced evaluation methods, techniques, and technologies - Biswas, Ashim Kumar; Mandal, Prabhat Kumar (Academic Press, an imprint of Elsevier, 2020)
Meat Quality Analysis: Advanced Evaluation Methods, Techniques, and Technologies takes a modern approach to identify a compositional and nutritional analysis of meat and meat products, post-mortem aging methods, proteome analysis for optimization of the aging process, lipid profiles, including lipid mediated oxidations, meat authentication and traceability, strategies and detection techniques of potential food-borne pathogens, pesticide and drug residues, including antimicrobial growth promoters, food preservatives and additives, and sensory evaluation techniques. This practical reference will be extremely useful to researchers and scientists working in the meat industry, but will also be valuable to students entering fields of meat science, quality and safety. --